Career Development Strategies: English Studentsâ€™ Interest Program at Muhammadiyah University of Tangerang - Euis Yanah Mulyanah; Husna Khofifah; Tarum Ningsih; Nanda Faradilla; Mila Adela (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
This study investigates the perceptions of career development among English language students. The study focuses on the interest of Muhammadiyah Tangerang University students who participated in workshop activities at Ahmad Dahlan University. The research was conducted through observation and questionnaires, and a total of 20 students were surveyed. The results of our observations indicate that 96% of the surveyed students had a positive perception of the benefits of the study tour to Jogja in supporting their careers based on their interests. Out of the 20 students surveyed, 80% expressed an interest in public speaking and opted for practical methods to develop their skills. The study's findings offer valuable insights into how educational institutions can better prepare their students to face the challenges of the constantly evolving world of work. The study presents practical training practices for students in various skills relevant to the tourismÂ industry.